2014
DOI: 10.1128/mcb.01285-13
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Follistatin Gene by RSPO-LGR4 Signaling via Activation of the WNT/β-Catenin Pathway in Skeletal Myogenesis

Abstract: WNT signaling plays multiple roles in skeletal myogenesis during gestation and postnatal stages. The R-spondin (RSPO) family of secreted proteins and their cognate receptors, members of leucine-rich repeat-containing G protein-coupled receptor (LGR) family, have emerged as new regulatory components of the WNT signaling pathway. We previously showed that RSPO2 promoted myogenic differentiation via activation of WNT/␤-catenin signaling in mouse myoblast C2C12 cells in vitro. However, the molecular mechanism by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
(86 reference statements)
1
29
0
1
Order By: Relevance
“…Follistatin is a functional antagonist of the TGF‐ β family that inhibits MSTN and induces skeletal hypertrophy . Moreover, follistatin has been used in gene therapy for myopathies due to its effects on the MSTN pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follistatin is a functional antagonist of the TGF‐ β family that inhibits MSTN and induces skeletal hypertrophy . Moreover, follistatin has been used in gene therapy for myopathies due to its effects on the MSTN pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Follistatin is a functional antagonist of the TGF-family that inhibits MSTN and induces skeletal hypertrophy. [21][22][23] Moreover, follistatin has been used in gene therapy for myopathies due to its effects on the MSTN pathway. 24 Another study demonstrated that follistatin is essential for skeletal muscle hypertrophy independently of MSTN.…”
Section: Discussionmentioning
confidence: 99%
“…INHBA , KIT , TGFB1 , and TGFB3 were upregulated while NT5E and FST were downregulated significantly in Jagged1‐treated hPDLs. Previous report suggested the strong possibility of cross‐talking between the WNT/β‐catenin and TGF‐β signaling pathways mediated by FST during myogenic differentiation (Han et al, ). NT5E is also known as CD73 .…”
Section: Discussionmentioning
confidence: 99%
“…RSPO2 promotes myogenic differentiation and myocyte fusion via activation of WNT/␤-catenin signaling in C2C12 cells (55). RSPOs can regulate WNT receptor expression and control myogenesis through gene expression of the transforming growth factor ␤ (TGF␤) antagonist Fst (56). Thus, WNT signaling is activated through WNT ligands, RSPO, and noncanonical (␤-catenin-independent) WNT signaling activators during muscle development.…”
Section: Discussionmentioning
confidence: 99%